Valuing those who care for others: the 'SafeSpace' project at Kibble - Mhairi Gallacher (Scottish Journal of Residential Child Care)
Maintaining and enhancing staff wellbeing is increasingly recognised as an essential aspect of effective residential child care. Children and young people receive the best care from adults who themselves are well supported. This article provides an overview of the 'SafeSpace' project at Kibble, which offers individual sessions to care staff to allow opportunities for reflection and emotional support within their role. Lessons learned from the project thus far, and questions for wider consideration across the sector are also discussed.